Study of 220kV 3 Core XLPE Submarine Cable using COMSOL Multiphysics - Lee, Wen Yi; Kamarudin , Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2021)
This paper presents a study and analysis of the electrical properties and electrical stress of a 220kV 3core XLPE insulated submarine cable. The model of electric cable is developed using COMSOL Multiphysics FEA software to simulate and determine the electrical properties such as capacitance, inductance, resistance, and power losses across the electric cable. The simulation model shows accurate results in capacitance compared to the analytical model. Inductance and resistance of cable greatly depend on the material and construction of the cable. Among all power losses, phase losses contribute the most due to skin effect and heat dissipation. Electrical stress data is determined as well through the plot of electric field distribution across the XLPE insulator. The plot shows an exponential decrease across the XLPE insulator with an initial maximum of 6.75MV/m electric field strength. Insulating medium must be selected with low permittivity constant to lower down the electric stress within the insulation layer.